Satisfaction with normative life domains and the course of anorexia nervosa. Issue 4 (25th February 2022) - van Doornik, Sanne F. W.; Ostafin, Brian D.; Jonker, Nienke C.; Glashouwer, Klaske A.; de Jong, Peter J.
Abstract: Objective: Satisfaction with normative life domains has been proposed as an important factor in the persistence of anorexia nervosa (AN). Initial evidence from a cross‐sectional study indicated that individuals with AN reported lower satisfaction with normative life domains than individuals without an eating disorder. As an important next step in understanding causal relations, the present study used a longitudinal design to examine whether an improvement in AN symptoms is paralleled by an increase in satisfaction with normative life domains from baseline to follow‐up and whether relatively low satisfaction with normative life domains at baseline is related to less improvement in AN symptoms. Methods: During baseline and at 1‐year follow‐up, adolescents with AN ( N = 69) completed the Brief Multidimensional Students' Life Satisfaction Scale to measure satisfaction with normative life domains (e.g., friendships, school experience). Furthermore, eating disorder symptoms and BMI were measured. Results: Improvement in eating disorder symptoms, but not in BMI, was paralleled by an increase in satisfaction with normative life domains. Relatively low satisfaction with normative life domains at baseline was not prospectively related to less improvement in eating disorder symptoms or BMI at follow‐up. Discussion: Our findings provide initial evidence that satisfaction with normative life domains is a malleable factor which fluctuates with symptom severity in AN. The results of this exploratory study point to the relevance of examining whether targeting satisfactory engagement with specific life domains optimizes treatment effectiveness. Public Significance: We explored whether an improvement in anorexia nervosa symptoms from start of treatment to 1‐year follow‐up would be paralleled by an increase in satisfaction with normative life domains. Improvement in eating disorder symptoms (but not BMI) was indeed related to a concurrent increase in satisfaction with normative life domains. These preliminary results point to the promising possibility that targeting satisfactory engagement with specific life domains may potentially enhance treatment effectiveness.